The Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Etnosains Untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa - Indah, Indah Permatasari; Hakim, Aliefman; Muntari, Muntari; Burhanuddin, Burhanuddin (FKIP University of Mataram, 2024)
This research aimed to develop a students ethics science worksheet that is appropriate (valid, practical, and effective) for improving students’ critical thinking skills. This development research was conducted based on 4D models (define, design, develop, and disseminate). The validity level of student’s ethics science worksheet was validated by 3 (three) validators obtained a result V of 0,79 with valid categories. The practicality level of students’ ethics science worksheet obtained persentase of 88,5% with very pratical categories. The effectivenes level of students’ ethics science worksheet in improving students’ critical thinking skills is shown by the results n-gain analysis of 0,62 with a persentase of 0,62% in the moderate categories and effective enough. Furthermore, for each aspect of the ability to think creatively, scores are obtained for aspects fluency, eleboration, flexibility, and originality with an average N-gain are 0,67, 0,58, 0,63, and 0,55. Thus it can be concluded that, the students’ ethics science worksheet is appropriate to use to improve students’ creative thinking skills.